Pengaruh Kualitas Layanan terhadap Kepuasan, Kepercayaan, dan Komitmen - Jefri Jefri; Petra Surya Mega Wijaya (Jurnal Riset Manajemen dan Bisnis, 2008)
This research examines three hypotheses, firstly, the effect of service quality on customer satisfaction, ,rrorily the effict oT rutto*ir sat;sfaction on trust and commitment, and finally the effict of trust on commitrnent. These examinations will be placed on retail sentice provider, namely, Carrefour Ambarulcrno Plaza, Yogyakana. The sample of this research is randomly drawn from 200 respondents. By using Structural Equation Modelins 6EM) the results shows that some of the hypotheses are supported. The four aspects of service quality which are responsiveness, assurance, empathy and tangible have a significant effect on customer satisfaction. Conversely, the other aspect of service quality, namely reliability does not affect customer satisfaction.Moreover, customer satisfaction significantly affects customer trust as well as trust on comminnent.Keywords: Service quality, satisfaction, trust, commitment, SEM, Carrefour